Analysis of Gross Motor Skills of Mentally Disabled Children at Dharma Bhakti Abcd Special School Class I-VI Ngempon Semarang Regency - Rosnita, Windha; Nilawati, Ika; Aristiyanto, Aristiyanto; Amin, Nur; Nur Islami, Ina Prihati; Nasri, Nasri (Journal of International Conference Proceedings, 2025)
Gross motor skills are crucial abilities for daily life that involve the use of large muscles. Children with mental disabilities often face limitations in physical and mental aspects, which can hinder their gross motor development. This study employed a quantitative descriptive design to describe conditions without testing hypotheses. Data were collected through tests of flexibility, coordination, strength, speed, and endurance among students in grades I–VI at Dharma Bhakti Abcd Special School, Ngempon, Semarang Regency. The results showed that both boys and girls achieved a 100% score in the “good” category for flexibility. In coordination, boys were largely in the “less” category (47.1%), while girls achieved 100% in the “good” category. Strength tests indicated both groups were in the “moderate” category (100%). For sprint ability, boys were mostly “moderate” (85.7%), while girls were divided into “good” (40%), “moderate” (40%), and “less” (20%). Endurance results showed both boys and girls in the “less” category (100%). Overall, the findings highlight strong flexibility but challenges in coordination and endurance, providing insights for educators and therapists in designing targeted interventions.